Digital Transformation of Financial Management through a Web-Based Accounting Information System at the Ratu Bhasma Bangkiang Sidem Tourist Attraction in Babahan Village, Tabanan Regency - Made Desmoon Gunawan; Muhammad Rohid Abdur Rohman; Komang Gede Tri Arta Wibawa; Ni Made Sri Rukmiyati; I Wayan Tuwi; Anak Agung Istri M. Septiviari (Transpublika Publisher, 2026)
The increasing need for efficient and transparent financial management has encouraged tourism destinations to adopt digital accounting systems. This study aims to design and implement a web-based accounting information system at the Ratu Bhasma Bangkiang Sidem Tourist Attraction in Babahan Village, Tabanan. The problem identified in this study is that financial record keeping is still conducted manually using handwritten notes and spreadsheet files, resulting in data duplication, recording errors, and delays in financial reporting. This study employs a qualitative descriptive method through observation and interviews with tourism managers and administrative staff. The developed system includes features such as a financial dashboard, transaction input forms, automated income and expense recording, cash balance monitoring, and real-time financial reporting. The system is capable of generating daily transaction reports, monthly income statements, cash flow reports, and printable financial summaries automatically. The implementation results indicate that the system improves the accuracy and efficiency of financial data processing, reduces the risk of human error, accelerates report preparation, and supports more structured, transparent, and accountable financial management at the tourist attraction.